Industrial assessment of radiofrequency and microwave radiations:Case study at electronic manufacturing industries in Penang. - Abdullah, Mohd Zaid (Universiti Sains Malaysia, 1995)
In electronic manufacturing industry, the applications of an equipment emitting radiofrequency radiation (RFR) are numerous and increasing. It is known that exposure to RFR at sufficiently high intensity and duration can produce a variety of adverse health effects.